Broken double-J stent in a 40-year-old male with a history of ureteral calculus - Nirja Thaker, MBBS; Rajasbala Dhande, MD, PHD; P.H. Parihar, MD, PHD; Bhargav Patel, MS (Radiology Case Reports, 2025)
A Double-J (DJ) stent is routinely used in urology to preserve ureteral patency following surgery, although prolonged use can result in problems such as migration, encrustation, and, in rare cases, stent disintegration. We discuss the case of a 40-year-old male who had undergone ureteral calculus surgery two years prior and was experiencing urinary dribbling and minor suprapubic discomfort. The imaging revealed a fragmented DJ stent with shards in the renal pelvis, mid-ureter, urinary bladder, and proximal urethra. Despite the absence of infection or substantial pyuria, the patient developed grade 2 hydronephrosis. The stent fragments were effectively removed via ureteroscopy. The probable cause of the stent fracture was determined to be prolonged stent indwelling, which most likely caused material fatigue. This example emphasizes the significance of regular follow-up and timely stent replacement to minimize issues associated with long-term indwelling stents, such as fragmentation, which can cause substantial morbidity if not managed. Prompt diagnosis and care are critical for avoiding serious consequences.